Teacher’s Use of a Drawing Workshop as a Method of Art Therapy - Orazalieva, Rsaldy B.; Bila, Olena O.; Pozdnyakova, Olena L.; Derevyanko, Nataliya V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The purpose of the study is to evaluate the effectiveness of a workshop in watercolour drawing by a future teacher of art as part of art therapy to improve mental state. Background: In modern conditions of development of the innovation and educational process in higher education in the specialties "Fine Arts" and "Design” special attention is paid to the acquisition of professional skills and abilities of students to work in the art space of the Planer. In this regard, master classes are widely used in classes in higher education institutions, but most training is aimed at acquiring professional writing with watercolour. Method: Workshop, as a quick and illustrative example in the performance of a watercolour etude by a teacher, is the strongest means of aesthetic impact, which is to show the secrets of drawing mastery, aesthetic techniques of working with watercolour, brush movements, the appearance of colour fillings, emphasizing a pictorial composition. Results: In the course of the study, it was determined that using a drawing workshop as art therapy is an effective way to improve the mental state. Art-therapeutic work evokes positive emotions, helps form a more active life position, emotionally valuable acceptance of partners, and cohesion. Conclusion: Fine art products constitute objective evidence of a person’s mood and thoughts, which allows them to be used to assessing the mental state.